PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL GAMIFIKASI TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 2 PEKANBARU - Tri Ningsih, Sari; Nurhuda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of digital learning media on students’ learning interest in Economics at SMA Negeri 2 Pekanbaru, the magnitude of the effect, and the obstacles encountered in its implementation. This research employed a quantitative approach using an experimental method. The research subjects were eleventh-grade social science students at SMA Negeri 2 Pekanbaru, who were divided into an experimental group and a control group. The research instrument was a learning interest questionnaire. Data analysis techniques included classical assumption tests and the Independent Samples t-Test.The results indicate that the use of digital learning media has a significant effect on students’ learning interest, as evidenced by a significance value of 0.000 (< 0.05). Digital learning media also show a considerable effect in increasing the learning interest of eleventh-grade social science students. The obstacles identified in the implementation of digital learning media include limited access to devices and internet connectivity, teachers’ readiness and competence, and time management in the learning process. Therefore, digital learning media can be used as an effective alternative to enhance students’ learning interest in Economics